(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
5G wireless communication have been a topic of vast research in recent years.Incidentaly in this covid pandemic period ongoing,the 5G wireless communication is more famous and happening topic altogether.Key technologies like Milimeterwave(mmwave),Massive MIMO,Beamforming,Artificial Intelligence(AI),Block chain adds more specific advantages in 5G wireless communication.The basic five foundations discussed here in 5G have given the communication a new horizon altogether in comparison to the 4G wireless communication. For base stations the major and important problem is to decide the optimal beamforming adjustment because they don’t have computationally powerful resources. But on-site optimization processes would take a lot of time framing schedule and power framing which the base stations can’t afford. To resolve this major problem, an external inputed data training or trained data can be given and only the prediction process might be left to the base station. Having achieving a pre-built machine learning based algorithm model would drastically reduce the time and power needed for beamforming optimization